2017
DOI: 10.1038/s41598-017-15378-6
|View full text |Cite
|
Sign up to set email alerts
|

Action Categorization in Rhesus Monkeys: discrimination of grasping from non-grasping manual motor acts

Abstract: The ability to recognize others’ actions is an important aspect of social behavior. While neurophysiological and behavioral research in monkeys has offered a better understanding of how the primate brain processes this type of information, further insight with respect to the neural correlates of action recognition requires tasks that allow recording of brain activity or perturbing brain regions while monkeys simultaneously make behavioral judgements about certain aspects of observed actions. Here we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
2
1
0
Order By: Relevance
“…In line with previous results showing monkeys can learn to discriminate grasping from non-grasping hand actions ( Nelissen and Vanduffel, 2017 ) and left vs right or forward vs backward walking actions ( Vangeneugden et al., 2010 ), with a certain degree of generalization to untrained exemplars, our current findings show monkeys are able to discriminate between grasp, touch and reach actions after training. Although we only trained with a small stimulus set for a limited period of time, both monkeys became proficient in the three-way discrimination task after 30 to 40 training sessions.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous results showing monkeys can learn to discriminate grasping from non-grasping hand actions ( Nelissen and Vanduffel, 2017 ) and left vs right or forward vs backward walking actions ( Vangeneugden et al., 2010 ), with a certain degree of generalization to untrained exemplars, our current findings show monkeys are able to discriminate between grasp, touch and reach actions after training. Although we only trained with a small stimulus set for a limited period of time, both monkeys became proficient in the three-way discrimination task after 30 to 40 training sessions.…”
Section: Discussionsupporting
confidence: 92%
“…The neural machinery underlying observed action processing revealed by the present study also suggests that area AIP should prove an ideal focus for future investigations into the neural basis of the monkeys’ ability to discriminate and categorize hand actions ( Nelissen and Vanduffel 2017 ), as previously investigated for 3D-shapes ( Verhoef et al 2015 ). Interestingly, this function may also benefit from the activity of suppression OMA-selective units that, unlike facilitation units, did not respond during grasping in the dark but did so in the light.…”
Section: Discussionsupporting
confidence: 55%
“…Some primate studies have been carried out on 1.5 T or 3 T scanners (Nelissen and Vanduffel 2017), with a sub-optimal resolution in the range of 2-3 mm. In vivo studies of structural brain imaging at 7 T have been reported in the rhesus macaque (Macaca mulatta), with resolution from 0.3 to 0.5 mm (Zitella et al 2015).…”
Section: State Of the Art At High Field Mrimentioning
confidence: 99%